A long-term follow-up of respiratory symptoms and ventilatory function in a group of working men. Issue 4 (October 1970) - Howard, Peter
Abstract : Howard, Peter (1970). Brit. J. industr. Med., 27, 326-333. A long-term follow-up of respiratory symptoms and ventilatory function in a group of working men. Out of a group of 289 industrial workers, 159 have been studied for a period of 11 years beginning in 1956. The mean rate of fall of FEV0·75 was 0·034 litre/year and the rate of fall of FVC was 0·064 litre/year. There was little change in the FEV% FVC over the period. Sudden drops of FEV were observed in a few men. Between 1956 and 1962 the number of men with regular sputum expectoration increased, but after 1962 more men lost this symptom than acquired it. The FEV was often markedly reduced by the time regular symptoms of bronchitis appeared. It seemed likely that symptomatic evidence of bronchial inflammation and infection and smoking were not related to the loss of ventilatory capacity in most men. Factors considered important to the genesis of airways obstruction, such as smoking, bronchial inflammation, atmospheric pollution and occupation, may differ in their importance in different environments. In this study atmospheric pollution was probably the most important factor.